Prevalence of Cryptosporidium spp. in Children with Diarrhea in the West Bank, Palestine - Sameer M. Abu-Alrub,1 Gabi M. Abusada,1,2 Mohammad A. Farraj,1 Tamer A. Essawi.1 (The Journal of Infection in Developing Countries, 2008)
This study was carried out to investigate the prevalence of Cryptosporidium spp. in children (n=760) with diarrhea aged 1 month to 13 years, living in urban areas (n=234), rural areas (n=394) and refugee camps (n=132). Samples were collected, stained by modified acid fast stain and examined microscopically for oocysts. The overall prevalence was 11.6% (88/760). The prevalence was higher in refugee camps 12.9% (17/132) and 12.2% (48/394) in rural areas as compared to 9.8% (23/234) in urban areas.According to age, the prevalence in age group I (<5 years) was significantly high (P<0.05) 14.4% (67/464) as compared to 7.7% (15/195) in age group II (5-10 years) and 5.9% (6/101) in age group III (10-15 years). Our finding indicated that the prevalence of Cryptosporidium spp. is high as compared to that in developed countries.